Non-violent Consumption - McGregor, Sue (In Factis Pax: Journal of Peace Education and Social Justice, 2016)
Non-violent right action is proposed as the most promising method of moving beyond capitalism and a consumer culture to a more humane society. After exposing the violence inherent within the consumer culture and the global marketplace (due to structural violence), this paper explains the main principles of non-violence (especially satyagraha, right actions, and the Truth), and then reframes consumption through a non-violent lens. Offering the satyagraha (drawing on an inner power reserve of self-Truth) is tendered as a progressive way for people to view themselves as consumers, thereby enabling them to engage in right actions in the marketplace. Non-violence is offered as a way to deal with the inequities of the global consumer marketplace and the infringements on the human condition, other species, and the Earth. Note: A different version of this paper was included as a Chapter 10 in my book titled Consumer Moral Leadership (Sense Publishers 2010).